Direct observation of the topological spin configurations mediated by the substitution of rare-earth element Y in MnNiGa alloy. Issue 5 (19th January 2018) - Zuo, S. L.; Zhang, Y.; Peng, L. C.; Zhao, X.; Li, R.; Li, H.; Xiong, J. F.; He, M.; Zhao, T. Y.; Sun, J. R.; Hu, F. X.; Shen, B. G.
Abstract : The spin configuration evolution due to the Y substitution and electromagnetic manipulation in MnNiGaY. Abstract : The evolution of topological magnetic domains microscopically correlates the dynamic behavior of memory units in spintronic application. Nanometric bubbles with variation of spin configurations have been directly observed in a centrosymmetric hexagonal magnet (Mn0.5 Ni0.5 )65 (Ga1− y Y y )35 ( y = 0.01) using Lorentz transmission electron microscopy. Magnetic bubbles instead of biskyrmions are generated due to the enhancement of quality factor Q caused by the substitution of rare-earth element Y. Furthermore, the bubble density and diversified spin configurations are systematically manipulated via combining the electric current with perpendicular magnetic fields. The magnetic bubble lattice at zero field is achieved after the optimized manipulation.